IMPLEMENTASI PENDEKATAN DIFERENSIASI DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII DI SMP AL MADINAH DIWEK JOMBANG - Aliyah Aqsowiyah; Khoirul Umam (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the context of Islamic Religious Education (PAI) learning at Al Madinah Junior High School in Diwek Jombang, the purpose of this study is to investigate the implementation of a differentiated approach to improve the learning outcomes of eighth-grade students. This research uses a qualitative approach with a case study design. Data collection techniques were carried out through interviews, observations, and documentation involving the school principal, PAI teachers, and students. The research focuses on two main aspects: the implementation of the differentiated approach in the learning process, and its impact on student learning outcomes. Based on the findings, PAI teachers at Al Madinah Junior High School apply a differentiated approach through variations in content, process, and learning products to align learning with students' readiness, interests, and learning styles. This strategy creates a more flexible and adaptive learning environment. As a result, the differentiation approach positively contributes to the improvement of students' academic performance as well as the strengthening of their religious character. In conclusion, the implementation of the differentiation approach has proven to be effective in supporting learning outcomes and the character development of students in the subject of PAI, although continuous evaluation and reinforcement are still necessary to optimize its implementation.